Analisis Putusan Pengadilan dalam Sengketa Administrasi Kepegawaian atau Sanksi Etik dalam Penyelenggaraan Pemilihan Umum di Indonesia - Siti Alya Cantika Nurjihan (Uniku Law Review, 2025)
This study examines the Jakarta Administrative Court Decision Number 285/G/2024/PTUN.JKT regarding the validity of the Bawaslu Chairperson's decision to impose employee sanctions as a follow-up to the Election Organizer Honor Council (DKPP) decision. The research method used in this study is a normative juridical research method. The results of the study found that the implementation of ethical decisions is indeed the authority of the Bawaslu chairperson but must still comply with the provisions of state administrative law and the principles of good governance. The panel of judges considered that the sanction decision in this case did not fully comply with procedures and limits of authority, so it can be tested and overturned by the PTUN. This decision emphasises that the implementation of ethical sanctions must uphold the principle of legality while protecting the rights of election organisers. In conclusion, the Bawaslu Chairperson does have the authority to impose employee sanctions as a follow-up to the DKPP ethical decision, but this authority must still be exercised in accordance with the provisions of state administrative law. Bawaslu's recommendations include clarifying and standardising the mechanism for implementing DKPP decisions, strengthening coordination with the DKPP, and ensuring that all personnel sanctions are implemented in accordance with the principles of legality, transparency, and protection of election organisers' rights to prevent similar disputes in the future.